2006
DOI: 10.1152/ajpcell.00426.2005
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological chaperone corrects lysosomal storage in Fabry disease caused by trafficking-incompetent variants

Abstract: Fabry disease is a lysosomal storage disorder caused by deficiency of alpha-galactosidase A (alpha-Gal A) resulting in lysosomal accumulation of glycosphingolipid globotriosylceramide Gb3. Misfolded alpha-Gal A variants can have residual enzyme activity but are unstable. Their lysosomal trafficking is impaired because they are retained in the endoplasmic reticulum (ER) by quality control. Subinhibitory doses of the competitive inhibitor of alpha-Gal A, 1-deoxygalactonojirimycin (DGJ), stabilize mutant alpha-Ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
89
0
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 115 publications
(94 citation statements)
references
References 38 publications
3
89
0
2
Order By: Relevance
“…Several groups have shown that 1-deoxygalactonojirimycin corrects the trafficking defect in six mutants of ␣-galactosidase A, the enzyme that is deficient in Fabry disease (17,18,30). This pharmacological chaperone binds to the active site of the enzyme at the neutral pH of the ER to assist folding and enhance transport out of this organelle, but it dissociates in the low-pH environment of the lysosome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several groups have shown that 1-deoxygalactonojirimycin corrects the trafficking defect in six mutants of ␣-galactosidase A, the enzyme that is deficient in Fabry disease (17,18,30). This pharmacological chaperone binds to the active site of the enzyme at the neutral pH of the ER to assist folding and enhance transport out of this organelle, but it dissociates in the low-pH environment of the lysosome.…”
Section: Discussionmentioning
confidence: 99%
“…The ability of several glucose and galactose analogs to increase the activity of the defective enzymes in Gaucher and Fabry disease cells, respectively, has been recently demonstrated by several groups (15)(16)(17)(18)(19)(20). Although the increased enzyme activity is believed to result from improved folding and trafficking of the mutant enzymes, insight into the actual mechanisms whereby these small molecules exert their action is limited.…”
mentioning
confidence: 99%
“…Previous studies have analyzed the subcellular site(s) of accumulation of misfolded proteins and shown that they may be stored throughout the ER (27) and may cause local dilatation or proliferation of the ER or induce proliferation of pre-Golgi intermediates (28)(29)(30)(31)(32)(33). However, the possible involvement of these induced structures in retrotranslocation of misfolded proteins remains enigmatic.…”
Section: Discussionmentioning
confidence: 99%
“…Both in vivo and in vitro studies of these diseases have elucidated the role of particular chaperone compounds in decreasing misfolded protein aggregation, enhancing proper trafficking of the protein(s) in question to target sites, and ameliorating the overall disease phenotype. The success of chaperones in other disorders, such as nephrogenic diabetes insipidus and Parkinson's disease, is encouraging [21,31,32,38,50]. However, to date, no published studies have examined the use of chemical chaperones as a treatment for AMD in humans or in AMD models.…”
Section: Similarities Between Amd and Other Neurodegenerative Diseasementioning
confidence: 99%
“…The treatment of other neuronal and age-related diseases with chemical and pharmacological chaperones provides the foundation for research into their applications in AMD [38,50]. Although, there is no clear target for chaperone treatment in AMD, increasing the expression of native molecular chaperones would likely help the cells respond to the stressed environment of the aging AMD macula.…”
Section: Similarities Between Amd and Other Neurodegenerative Diseasementioning
confidence: 99%